RELATIVE CLAUSE OMISSION FOUND IN TENET MOVIE BY CHRISTOPHER NOLAN - Octavian, Hermanda; Handayani, Nurma Dhona (IdeBahasa, 2024)
This descriptive qualitative research aimed to identify instances of relative clause omission in the movie Tenet by director Christopher Nolan. A theory from Hewings (2013) was applied to determine relative clauses in the data source. Observation and documentation were used as data collection methods, with the analysis conducted descriptively using words and sentences. Out of the 44 utterances that contain relative clauses, there were 20 data represented relative clause omission found in the movie's dialogues. They were categorized by subordinator: 7 utterances omitting "who", 3 utterances omitting "whom", 9 utterances omitting "that/which", 1 utterance omitting “why”, and 2 utterances omitting “when”. Only 10 data were selected as samples to narrow down the analysis. After thoroughly conducting the research, it was concluded that the omission of clauses, including relative clauses, often occurred in the context of informal conversations such as those found in movies. Although the omission made the utterances grammatically incomplete, it did not stop listeners from understanding them, as the meanings of the utterances remained the same.